PERSEPSI SISWA TERHADAP EFEKTIVITAS PROSES BELAJAR MENGAJAR DAN HUBUNGANNYA DENGAN HASIL BELAJAR MATEMATIK: PERSEPSI SISWA TERHADAP EFEKTIVITAS PROSES BELAJAR MENGAJAR DAN HUBUNGANNYA DENGAN HASIL BELAJAR MATEMATIK - May Fitriana Hasibuan (Information Technology and Science (ITScience), 2019)
Abstract Mathematics as one part of education that must be learned by each student in formal institutions. Mathematics is also one of the fields of study that has an important role and many of us meet in everyday life. So there is no doubt that mathematics is one of the pinnacles of intellectual glory. Etymologically the perception comes from English, namely